Linking Behavior, Co-infection Patterns, and Viral Infection Risk With the Whole Gastrointestinal Helminth Community Structure in Mastomys natalensis - Vanden Broecke, Bram; Bernaerts, Lisse; Ribas, Alexis; Sluydts, Vincent; Mnyone, Ladslaus; Matthysen, Erik; Leirs, Herwig (Frontiers in Veterinary Science, 2021)
Infection probability, load and community structure of helminths varies strongly between and within animal populations. This can be ascribed to environmental stochasticity or due to individual characteristics of the host such as their age or sex. Other, but understudied, factors are the hosts’ behavior and co-infection patterns. In this study, we used the multimammate mouse (Mastomys natalensis) as a model system to investigate how the hosts’ sex, age, exploration behavior and viral infection history affects their infection risk, parasitic load and community structure of gastrointestinal helminths. We hypothesized that the hosts’ exploration behavior would play a key role in the risk for infection by different gastrointestinal helminths, whereby highly explorative individuals would have a higher infection risk leading to a wider diversity of helminths and a larger load compared to less explorative individuals. Fieldwork was performed in Morogoro, Tanzania, where we trapped a total of 214 individual mice. Their exploratory behavior was characterized using a hole-board test after which we collected the helminths inside their gastrointestinal tract. During our study, we found helminths belonging to eight different genera: Hymenolepis sp., Protospirura muricola, Syphacia sp., Trichuris mastomysi, Gongylonema sp., Pterygodermatites sp., Raillietina sp. and Inermicapsifer sp. and one family: Trichostrongylidae. Hierarchical modelling of species communities was used to investigate the effect of the different host-related factors on the infection probability, parasite load and community structure of these helminths. Our results show that species richness was higher in adults and in females compared to juveniles and males, respectively. Contrary to our expectations, we found that less explorative individuals had higher infection probability with different helminths resulting in a higher diversity, which could be due to a higher exposure rate to these helminths and/or behavioral modification due to the infection.